ANALISIS MAKNA TRADISI BARONG IDER BUMI DI DESA KEMIREN KABUPATEN BANYUWANGI - Indah, Tantri Laroiba; Setyawan, Bagus Wahyu (Jurnal Bahasa, Sastra, dan Budaya, 2022)
The Barong Ider Bumi tradition in Kemiren Banyuwangi is a traditional ceremonial tradition that is held every year by the Osing Banyuwangi community. This tradition is a village clean ritual as an expression of gratitude to God Almighty and to ward off disease. The people of Banyuwangi also believe that if it is not implemented, there will be disasters such as crop failure and disease outbreaks so that this earth barong ider tradition becomes something that the Osing Banyuwangi community feels obligated to do. The aims of this research are to find out and examine the early history of the earth barong ider tradition in Kemiren village, Banyuwangi district, to find out systematically about the implementation of the earth barong ider ceremony, and to find out and study more deeply about the meaning and purpose of the barong ceremony tradition. ider earth in Kemiren village, Banyuwangi district.